Traffic mortality of wild forest reindeer Rangifer tarandus fennicus in Finland - Milla Niemi; Sari C. Cunningham; Robert Serrouya; Veli-Matti Väänänen; Sakari Mykrä-Pohja (Nature Conservation)
Vehicle collisions kill at least one million ungulates annually in Europe. The number of traffic-killed individuals is usually relatively low for managed species, compared to the annual harvest quota. Therefore, traffic mortality in common ungulate species has historically been seen as a management and traffic safety problem, rather than a conservation issue. However, rare ungulate species, such as European wild forest reindeer (WFR) Rangifer tarandus fennicus, challenge this paradigm. The global population of WFR is approximately 5 300 individuals, divided into three main subpopulations: Suomenselkä and Kainuu in Finland, and N-W Russia. WFR females generally produce only one calf per year, which makes this species particularly vulnerable to any additional source of mortality. Here, we investigate traffic mortality of WFR in Finland. For both Finnish WFR subpopulations we estimated a kill rate (the proportion of individuals killed/struck) and, in relation to their winter population sizes, the collision and traffic mortality rates. Our collision data was collected during 2017–2022 by volunteer hunters and consisted of 390 road traffic collisions (407 WFR individuals), with supplementary data on railway collisions. In total, 259 individuals were killed directly in road traffic collisions or euthanized later after tracking (kill rate 64%). An age class (adult/juvenile) was determined for 265 animals (65%), and the results indicated that noticeably more adults than juveniles were killed. In relation to wintering subpopulation sizes, there were higher collision and traffic mortality rates in Suomenselkä (3.0% and 2.0% of the winter population, respectively) than in Kainuu (1.8% and 1.3%). WFR-train collisions occurred in both subpopulations. In Suomenselkä, a railway mortality rate of 0.2% was recorded, while in Kainuu it was 0.7%. We found collision and traffic mortality rates that were relatively low and comparable with those of other ungulate species. However, the relatively high proportion of adults observed among road-killed individuals lends support for further studies to develop species-specific mitigation measures for WFR.